Implications of Ultrasonography in the Diagnosis and Management of Patients Presenting with Non-Traumatic Acute Abdominal Pain in a Tertiary Hospital of Mid-Western Region of Nepal - Ghimire, Prasanna; Paudel, Nabin; Koirala, Dwight; Singh, Bhuwaneshwar Prasad (Nepalese Journal of Radiology, 2018)
Introduction: Acute abdomen is the most common condition for patients presenting in the emergency. Ultrasound among other imaging modalities is the most common diagnostic tool employed in the diagnosis of such cases. Methods: A prospective study of consecutive patients presenting with acute abdomen fulfilling the inclusion and exclusion criteria were included in the study. Ultrasound was performed by single radiologist and findings were correlated to the clinical, pathological and surgical findings. Results: A total of 248 patients fulfilled all criteria and were included in the study. The age of patients ranged from 15-62 years with mean age of 41.3 years. There was female predominance with a male to female ratio of 1:1.8. Ultrasound accurately diagnosed 233 cases (93.9 %). Urolithiasis was the most common finding (45.16%) followed by acute appendicitis (19.35%). Conclusion: Ultrasound has pivotal role in the diagnosis and overall management of patient presenting with acute abdomen. Urolithiasis is the most common etiology for non- traumatic acute abdomen.